Desenvolvimento de um Apontador Estelar para o ensino de astronomia - Pedersen, Fernando Augusto (Universidade Federal de São Carlos, 2018)
By analyzing the optoelectronic equipments available for the teaching of astronomy, it was observed that there is no equipment that uses a beam of laser light commanded by a computer for orientation in sky observations. For this reason, this monograph aimed to develop a stellar pointer, entitled as Star Pointer. This equipment will indicate, through a beam of light emitted by a laser, the location of astronomical objects. The Star Pointer was developed at a low cost, approximately R$ 182.20, promoting observations of the sky, improving the learning in Astronomy. All software used to develop Python and Arduino programs are free and easily accessible. In order to assemble the hardware components, in-depth knowledge of electronics is not necessary. The results found in the equipment tests are encouraging, although there is a need for improvements in the software developed in Python. The equipment has a good response in the commands that are inserted and its functions are quite comprehensive. The possible commands to be carried out are: several trajectories; outline of celestial objects; indication of stars in a constellation and combinations of these commands. These commands make it possible to carry out simple activities as indicating a celestial object, and more elaborate ones as the contour of each star in a constellation. Improvements and corrections of the software are already being carried out, they aim to make the equipment more versatile and the use of the smartphone in place of the computer, making it more accessible.
Development of a Star Pointer for astronomy teaching
Keywords: Astronomia; Apontador estelar; Laser; Ensino; Astronomy; Star Pointer; Teaching; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::TECNOLOGIA EDUCACIONAL